2022
DOI: 10.1111/rda.14196
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular dynamics, hormonal profiles and ovulation time in Mithun cows (Bos frontalis)

Abstract: The study aimed to evaluate follicular dynamics and concentrations of estradiol-17β (E2), progesterone (P4), follicle stimulating hormone (FSH) and luteinizing hormone (LH) during the oestrous cycle and to determine ovulation time in Mithun cows. Ovaries of experimental cows (n = 7) were examined daily by transrectal-ultrasonography for three consecutive oestrous cycles (n = 21). The characteristics of follicular waves, dominant follicle, largest subordinate follicle and corpus luteum and ovulation time were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Mithun exhibits either compact or cavitory corpus luteum (CL) and undergoes luteolysis with an appearance of estrus upon administration of a luteolytic dose of PGF2α (Ramesh et al, 2022). The luteolytic dose of PGF2α induces luteolysis after day 5 to 6 days similar to cattle (Wenzinger & Bleul, 2012).…”
Section: Applications Of Arts In Mithunmentioning
confidence: 99%
See 4 more Smart Citations
“…Mithun exhibits either compact or cavitory corpus luteum (CL) and undergoes luteolysis with an appearance of estrus upon administration of a luteolytic dose of PGF2α (Ramesh et al, 2022). The luteolytic dose of PGF2α induces luteolysis after day 5 to 6 days similar to cattle (Wenzinger & Bleul, 2012).…”
Section: Applications Of Arts In Mithunmentioning
confidence: 99%
“…In Mithun, female and male reproductive physiology has been studied in detail (Dhali et al, 2006; Perumal, De, et al, 2021). The length of the estrous cycle is in the range of 20–25 days with a longer duration of oestrus (50–67 h) and no distinct visible or behavioural signs of estrus (silent estrus) (Dhali et al, 2006; Ramesh et al, 2022). A recent study on follicular dynamics and hormonal profiles revealed that Mithun cows exhibit two, three and four follicular waves with a preponderance of three follicular waves (Ramesh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations